(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Phishing attack is the simplest way to obtain sensitive information from innocent users. Aim of the phishers is to acquire critical information like username, password, and bank account details. Cyber security persons are now looking for trustworthy and steady detection techniques for phishing websites detection. This project deals with machine learning technology for detection of phishing URLs by extracting and analyzing various features of legitimate and phishing URLs. In addition, the main motive of this research is to detect phishing URLs as well as narrow down to best machine learning algorithm by comparing accuracy of each algorithm.